Pengaruh Pelatihan Literasi Digital terhadap Kemampuan Literature Searching Mahasiswa Baru Program Pasca Sarjana Universitas ‘Aisyiyah Yogyakarta - Irkhamiyati Irkhamiyati; Lilik Layyina (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2019)
The development of the internet provides a lot of information that is easily accessible, but many new students feel confusion in using it, including the information provided by the library (library anxiety). The ability to identify, access, evaluate and ethically use information is very important, so information literacy skills are needed to realize the ability of literature searching. Digital literacy is part of information literacy to overcome library anxiety. This study aims to determine the implementation of digital literacy training and literature searching abilities of new students of ‘Aisyiyah Yogyakarta University Postgraduate Program, as well as the influence of both. The type of this research is correlational using a quantitative approach. Data collection techniques using observation, documentation, interviews, and questionnaires. Data analysis is done by testing the validity, reliability, normality, linearity, and hypothesis. ADDIE (Analysis, Design Development, Implementation, Evaluation) models are used to assess the implementation of training. The results showed that the implementation of digital literacy training and the ability of literature searching of students with a good grades. Hypothesis testing shows that there is an effect of digital literacy training on the ability of literature searching. The recommended things are upgrading the material, preparing supporting facilities for training, and the suggestion that the training also be given to other students in order to realize ability of literature searching for all students in the University of ‘Aisyiyah Yogyakarta. Keywords: training, digital literacy, capabilities, literature searching, library axtiety, University of ‘Aisyiyah Yogyakarta.